Relationship Marketing in Banking Sector – A Comparison Between Public and Private Banks - Kumar, Deepak; Arora, Priya (Gyan Management Journal, 2023)
Relationship marketing is the wide concept and important in  modern times for better competition in the recent times. Berry  (1983) introduced the term relationship marketing. Later on many  research and debates conducted on the relationship marketing and the  challenges and major issues faced by the service provider in order to  maintain their customers. This paper attempt to summarize the Impact  of relationship marketing on banking sector and comparison is made  in order to understand about the status of relationship marketing in  public and private banks.
Keywords: Relationship Marketing; Private Banks